1996
DOI: 10.1128/jb.178.9.2580-2585.1996
|View full text |Cite
|
Sign up to set email alerts
|

Specific in vivo protein-protein interactions between Escherichia coli SOS mutagenesis proteins

Abstract: One of the components of the RecA-LexA-controlled SOS response in Escherichia coli cells is an inducible error-prone DNA replication pathway that results in a substantial increase in the mutation rate. It is believed that error-prone DNA synthesis is performed by a multiprotein complex that is formed by UmuC, UmuD, RecA, and probably DNA polymerase III holoenzyme. It is postulated that the formation of such a complex requires specific interactions between these proteins. We have analyzed the specific protein-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 54 publications
5
27
1
Order By: Relevance
“…Similar results were observed for UmuD, consistent with our hypothesis that UmuD and UmuDЈ might make similar contacts with UmuC. Furthermore, our finding that UmuD and UmuDЈ retained limited abilities to interact with all four derivatives of MBP-UmuC is consistent with the finding by Jonczyk and Nowicka (14) that N-terminal sequences of UmuC may also important for its interaction with UmuDЈ.…”
Section: Vol 183 2001supporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were observed for UmuD, consistent with our hypothesis that UmuD and UmuDЈ might make similar contacts with UmuC. Furthermore, our finding that UmuD and UmuDЈ retained limited abilities to interact with all four derivatives of MBP-UmuC is consistent with the finding by Jonczyk and Nowicka (14) that N-terminal sequences of UmuC may also important for its interaction with UmuDЈ.…”
Section: Vol 183 2001supporting
confidence: 82%
“…Although Jonczyk and Nowicka did not detect an interaction between UmuD and UmuC in vivo using the yeast two-hybrid system, they did detect an interaction between UmuDЈ and UmuC (14). Furthermore, they reported that small deletions of either N-or C-terminal sequences of UmuC destroyed its ability to interact with UmuDЈ as measured with the yeast two-hybrid system (14).…”
Section: Resultsmentioning
confidence: 99%
“…47). Interestingly, it has been reported that UmuC interacts with UmuDЈ, but not with UmuD, in the yeast two-hybrid system (45). In our case, MucB was found to interact both with MucA and MucAЈ.…”
Section: Discussionsupporting
confidence: 49%
“…It was previously shown that the UmuDЈ and UmuD proteins form both homo-and heterodimers when assayed biochemically (35,36,45) and in the yeast two-hybrid system (45). Here we show that MucAЈ and MucA behave similarly and exhibit both self-interactions and an interaction with each other.…”
Section: Discussionmentioning
confidence: 50%
“…The UmuDЈ 2 homodimer then interacts with UmuC (18,59,68), which has an ability to catalyze the formation of phosphodiester bonds, in such a way that the UmuDЈ 2 C complex is able to participate in TLS (43). In addition to participating in TLS, UmuC together with the full-length UmuD 2 homodimer participates in a DNA damage checkpoint control that acts to regulate DNA replication in response to DNA damage, thereby allowing additional time for nucleotide excision repair to accurately remove lesions in the DNA prior to continued replication (37).…”
mentioning
confidence: 99%